A Modern Chinese-English dictionary - Wai yu jiao xue yu yan jiu chu ban she. Ci dian bian ji shi. (Beijing Shi : Wai yu jiao xue yu yan jiu chu ban she : Xin hua shu dian Beijing fa xing suo, 1988)
1. Chinese-English--Dictionary
Includes bibliographical references (p. [6]).
Keywords: Chinese language -- Dictionaries -- English